PERENCANAAN PROGRAM PENDIDIKAN ISLAM BERBASIS ASESMEN KEBUTUHAN DALAM MENENTUKAN PRIORITAS PENGEMBANGAN MADRASAH: STUDI KEPUSTAKAAN - Alfisyah; Ahmad Salabi; Yahya Mof (PT. Hasba Edukasi Mandiri, 2026)
The quality of madrasah development planning in Indonesia remains largely inadequate due to the absence of systematic needs assessment as its foundation. This library research study aims to: (1) map the concepts and models of needs assessment in Islamic education; (2) analyze the patterns of needs assessment-based program planning in madrasahs; and (3) identify the development priorities for madrasahs that can be formulated through a needs assessment approach. Data were collected through systematic documentary analysis from primary sources (SINTA-accredited journals and official documents of the Ministry of Religious Affairs of the Republic of Indonesia) and secondary sources including reference books on Islamic education management. Data analysis employed content analysis, comparative analysis, and conceptual synthesis. Three key findings emerged. First, five relevant needs assessment models were identified: Gap Analysis, SWOT-based Needs Analysis, the Witkin- Altschuld Three-Phase Model, the Kaufman Organizational Elements Model (OEM), and Participatory Needs Assessment; a hybrid approach combining two or more of these models proved more effective than any single model applied in isolation. Second, needs assessment-based planning follows a cyclical five-phase pattern (diagnosis, prioritization, program formulation, implementation, and evaluation), yet the evaluation and feedback phase remains largely neglected in madrasah practice. Third, five clusters of development priorities were identified in order of urgency: human resource development, curriculum development, infrastructure and financing, institutional governance, and community partnerships. These findings are synthesized into the Islamic Education Planning Based on Needs Assessment Model (MP-PIBAK), which constitutes the theoretical contribution of this study and serves as a practical reference for madrasah principals, school supervisors, and policymakers at the Ministry of Religious Affairs of the Republic of Indonesia.